Thymic Dermoid Cyst: A Rare Anterior Mediastinal Mass - Reza Afghani; Roozbeh Cheraghali; Mahshid Mehrjerdian; Hanieh Raghimi; Sina Mohajernoei (Golestan University Of Medical Sciences, 2021)
Background: Thymic epidermoid cysts are very rare. These masses arise from migration of ectodermal cells into the tissue that does not contain these cells. The imaging findings are non-specific and surgical excision is required to reach definitive diagnosis. Case description: We describe an asymptomatic woman in her early 40s with an anterior mediastinal mass detected in the spiral chest CT scan for COVID 19. She underwent thymectomy and the histopathological exam revealed a dermoid cyst in thymus gland. Conclusion: The dermoid cysts etiology is unknown and there are many unproven theories. The clinical sign, symptoms and location of the cyst can be variable. Our case was asymptomatic and the cyst was accidently found in the imaging. The initial diagnosis was a thymoma and at the patient's insistence, cystectomy was performed and pathological findings indicated a thymic dermoid cyst.